NILAI PENDIDIKAN DALAM KESENIAN RENGKONG DI CIANJUR JAWA BARAT: KAJIAN ETNOPEDAGOGI - Ningsih, D. Nurfajrin; Cysbya Erdlanda, Febry Marindra (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2018)
This research are to describe the strucures and the etnopedagogy values in the Renkong arts in Cianjur, West Java. This research used descriptive analytical method with qualitative approach. The data were obtained from observation and interview. Findings show : (1) in the structure Rengkong can be found the history of Rengkong, the stage of Rengkong activities, the background location of Rengkong, the performers, the show time, the dance, the music, the equipment and the costume. (2) the etnopedagogic values that exist in Rengkong are, six human morals (human moral to God, the human moral to himself, the human moral to human, moral to nature, the human moral to time, and the human moral to reach physical and spiritual peace), caturdiriinsani (rich knowledge, obedient to religion, cultured, and skilled); and also gapurapancawaluya (healthy, kind, right, smart, and active. The etnopedadogic values found are life , education, moral, religion , and social.